THE EFFECT OF PROGRESSIVE RELAXATION THERAPY ON ELDERLY WITH INSOMNIA - Sutrisno - Sutrisno; Vitri Dyah Herawati; Atik Aryani (Jurnal Keperawatan Respati Yogyakarta, 2022)
Along with many physiologic changes seen with aging, significant changes also happen in sleep and circadian rhythm across the lifes. Insomnia is a form of sleep disorder that is often experienced by the elderly. Insomnia is difficulty initiating or maintaining sleep. Treatment for insomnia usually begins with the elimination of habits (moving beds, using the bed only to sleep and others) if it doesn't work, it can be treated with hypnotic drugs. In fact, the elderly with all the functional decline of their bodies will make the work of their organs more difficult when they often consume these drugs. Therefore a therapy that is progressive relaxation therapy is expected to overcome these problems in the elderly. Progressive relaxation provides a way to identify specific muscles to differentiate between feelings of tension and deep relaxation. The purpose is to analyzing the effect of progressive muscle relaxation to elderly with insomnia in Pucangan Village, Kartasura. This study uses a pre-experimental approach with a one-group pre-test and post-test design. Techniques Sampling was done by purposive sampling technique as many as 30 elderly people who suffer from insomnia. The statistical test used was the paired samples t test with a p value of < 0.05. The results using the paired t test show the mean value of the pretest was 13.10 with a standard deviation of 5.08 and the post-test value was 11.07 with a standard deviation of 5.09, with the result p value = 0.001. The conclusion in this study shows that progressive relaxation therapy has a significant effect on the elderly who experience insomnia. Keywords: Elderly; Insomnia; Progressive Relaxation